MALAT1 Promotes Tumorigenesis and Increases Cellular Sensitivity to Herceptin in HER2-positive Breast Cancer - Yang, Chuansheng; Zhu, Hongbo; Tan, Yeru; Zhu, Renjie; Wu, Xiaoping; Li, Yuehua; Wang, Cunchuan (Current Cancer Drug Targets, 2021)
Background: The function of MALAT1, a long non-coding RNAs (lncRNA), in HER2- positive breast cancer remains largely unexplored. Objectives: This study aimed to investigate the effect of MALAT1 on tumor development in HER2-positive breast cancer. Methods: We detected MALAT1 expression in HER2-positive breast cancer cells and tissues, and analyzed the effects of MALAT1 on cell proliferation in HER2-positive breast cancer cells lines (BT-474 and SKBR3). A mouse xenograft model was established for detecting the function of MALAT1 in HER2-positive breast cancer. Results and Discussion: As a result, MALAT1 was remarkably up-regulated in HER2-positive breast cancer both in cells and tissues. In addition, the silencing of MALAT1 inhibited the proliferation of HER2-positive breast cancer cells both in vitro and in vivo. Furthermore, knockdown of MALAT1 by shRNA down-regulated DNMT1, DNMT3a, and DNMT3b, while up-regulated BRCA1 and PTEN in HER2-positive breast cancer both in cell lines and mouse xenograft models. Conclusion: In short, MALAT1 might be a potential biomarker and therapeutic target for HER2- positive breast cancer therapy.
Keywords: long non-coding RNA